Programmable molecular composites of tandem proteins with graphene oxide for efficient bimorph actuators. (July 2017) - Vural, Mert; Lei, Yu; Pena-Francesch, Abdon; Jung, Huihun; Allen, Benjamin; Terrones, Mauricio; Demirel, Melik C.
Abstract: The rapid expansion in the spectrum of two-dimensional (2D) materials has driven research efforts on the fabrication of 2D composites and heterostructures. Highly ordered structure of 2D materials provides an excellent platform for controlling the ultimate structure and properties of the composite material with precision. However, limited control over the structure of the matrix phase and its interactions with highly ordered 2D materials results in defective composites with inferior performance. Here, we demonstrate the successful synthesis, integration, and characterization of hybrid 2D material systems consisting of tandem repeat (TR) proteins inspired by squid ring teeth and graphene oxide (GO). The TR protein layer acts as a unique programmable assembler for GO layers with precise control of interlayer distance of less than 1 nm. As an application, we further demonstrate thermal actuation using bimorph molecular composite films. Bimorph actuators made of molecular composite films (GO/TR) can lead to energy efficiencies 18 times higher than regular bimorph actuators consisting of a GO layer and a TR protein layer (i.e., conventional bulk composite of GO and TR). Additionally, molecular composite bimorph actuators can reach curvature values as high as 1.2 cm −1 by using TR proteins with higher molecular weight, which is 3 times higher than conventional GO and TR composites. Graphical abstract: